Foldable Electrode Architectures Based on Silver‐Nanowire‐Wound or Carbon‐Nanotube‐Webbed Micrometer‐Scale Fibers of Polyethylene Terephthalate Mats for Flexible Lithium‐Ion Batteries. Issue 7 (22nd December 2017) - Hwang, Chihyun; Song, Woo‐Jin; Han, Jung‐Gu; Bae, Sohyun; Song, Gyujin; Choi, Nam‐Soon; Park, Soojin; Song, Hyun‐Kon
Abstract: A crumply and highly flexible lithium‐ion battery is realized by using microfiber mat electrodes in which the microfibers are wound or webbed with conductive nanowires. This electrode architecture guarantees extraordinary mechanical durability without any increase in resistance after folding 1000 times. Its areal energy density is easily controllable by the number of folded stacks of a piece of the electrode mat. Deformable lithium‐ion batteries of lithium iron phosphate as cathode and lithium titanium oxide as anode at high areal capacity (3.2 mAh cm −2 ) are successfully operated without structural failure and performance loss, even after repeated crumpling and folding during charging and discharging. Abstract : Crumply superflexible lithium‐ion batteries based on current‐collector‐free and binder‐free nanowire‐around‐microfiber electrode architectures are presented. The battery cells of high loading density at 3.2 mAh cm −2 are successfully operated under folding, crumpling, and even hammering.